#TITLE_ALTERNATIVE# - IMANIITA INTAN SAFITRI (NIM : 10209072),
Seismic refraction method common to be used in geotechnical and environmental exploration. Seismic refraction method is one of geophysical method used for near-surface geological structure interpretation using travel time of seismic. Seismic refraction method needs geophone as it receiver and active source from hammer or explosive. P-wave more common to be used in seismic refraction method as it easier to detect in receiver. P- wave has fastest velocity than other seismic wave that detected first in receiver. Generalized Recicprocal Method (GRM) is an inversion technique in seismic refraction for mapping near-surface structure from forward and reverse shots travel time. GRM is the most advance method in seismic refraction available nowadays. Not like other interpretation method, GRM not smoothing the refract data. Results of seismic data processing using GRM more detail than other interpretation methods.